Equality of rights or heteronormativity? Teachers in the face of homosexuality (Práxis Educativa, 2019)
In daily school life, teachers face issues they do not have the opportunity to reflect upon or study more intensively. Among those, homosexuality is a topic that challenges them, especially when they are forced to reflect more actively through images and movies and not just through reading theoretical productions. Thus, this paper analyzes positions on homosexuality registered in an online discussion forum by schoolteachers of the Basic Education of the Federal District, Brazil, in the context of an in-service training course. In general, it was observed that heteronormativity is taken as a matrix that is organized in a binary and asymmetric way, with regulatory and uniformizing effect of the social environment and that produces stigmatization. The analysis of the records, based on the Documentary Method, also revealed the existence of three different types of orientation regarding homosexuality among the 140 teachers who participated in the in-service training: denial, review of their positions and defense of homosexuality. These distinct orientations reveal the weight of heteronormativity in the construction of an education that seeks to defend equality of rights.Keywords: Heteronormativity. Homosexuality. Homophobia in school. Equal rights. Diversity in education. Teacher in-service training.